Assessing the Effectiveness of Indonesia’s Energy Transition Through the Development of a Battery Electric Vehicle Ecosystem: Menilai Efektivitas Transisi Energi Indonesia Melalui Pengembangan Ekosistem Kendaraan Bermotor Listrik Berbasis Baterai - Siombo, Marhaeni Ria; Adi, Emmanuel Ariananto Waluyo (Universitas Islam Indonesia, 2025)
Indonesia aims to achieve Net Zero Emission (NZE) by 2060 through various initiatives, notably the Battery-Based Electric Vehicle (BBEV) program for road transportation. This study identifies opportunities and challenges in Indonesia’s energy transition via BBEV adoption. A normative juridical approach was employed, utilizing primary legal materials (laws, presidential and ministerial regulations) alongside secondary sources from government reports and academic literature. Findings reveal that public charging infrastructure (SPKLU/SPBKLU) remains far below the 2030 target, financing mechanisms for the BBEV ecosystem are suboptimal, and regulatory fragmentation persists across sectors (local content requirements, fiscal incentives, and battery waste management). To foster BBEV uptake, the Government should enhance banking sector engagement, harmonize inter-ministerial regulations, and expedite the issuance of technical rules and pro-consumer fiscal incentives.